Mantra Pemikat dalam Kisah Baridin Ratminah dari Cirebon Ditinjau dalam Perspektif Pendidikan Islam - Eddy Saputra (Universitas Indraprasta PGRI Jakarta, 2023)
The story of Baridin and Ratminah is so phenomenal in Cirebon society. the plays on the radio or stage performances to local films often present the story. Even though this is a legend by the people of Cirebon, the two figures seem to have lived, this is evidenced by the existence of a tomb in the name of Baridin in Jagapura Village, Cirebon Regency. Baridin's attempt, who had a desire to marry Ratminah, was rejected, accompanied by harsh treatment and insults at his mother. This incident made Baridin hurt and thought of making Ratminah fall in love with him. Baridin studied with his best friend in Jagapura Village and was given a charm spell to make Ratminah fall in love with him, but that was just an attempt at revenge. They both never got married until the end of his life. This study reviews the charm spells in an Islamic perspective. This research uses a qualitative descriptive method, where the resulting data is in the form of actual conditions that occur in the field. The purpose of this research is to provide knowledge that every time you want to achieve something, use reasonable methods so that no one feels hurt. The results of this study are to make the values of Islamic Education always a guide in all aspects of life.